2017
DOI: 10.1002/2016wr020005
|View full text |Cite
|
Sign up to set email alerts
|

The importance and challenge of hyporheic mixing

Abstract: The hyporheic zone is the interface beneath and adjacent to streams and rivers where surface water and groundwater interact. The hyporheic zone presents unique conditions for reaction of solutes from both surface water and groundwater, including reactions which depend upon mixing of source waters. Some models assume that hyporheic zones are well‐mixed and conceptualize the hyporheic zone as a surface water‐groundwater mixing zone. But what are the controls on and effects of hyporheic mixing? What specific mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 173 publications
(221 reference statements)
0
88
0
Order By: Relevance
“…It also can be seen that the 2D simulation has areas with large contrasting activities due to the local up‐ and downwelling flow cells caused by the spatial variation of surface heads along the streambed interface. Such concentration gradients are unlikely to arise in a 1D model, but are an important part of dispersive mixing in 2D and 3D flow in the hyporheic zone (Hester et al ). The modeled sequences also show features such as the “chimney effect” (Azizian et al ) where deep old upwelling hyporheic water enters the stream with little interaction with shallow flow cells (at e.g., ∼5 and 10 m).…”
Section: Resultsmentioning
confidence: 99%
“…It also can be seen that the 2D simulation has areas with large contrasting activities due to the local up‐ and downwelling flow cells caused by the spatial variation of surface heads along the streambed interface. Such concentration gradients are unlikely to arise in a 1D model, but are an important part of dispersive mixing in 2D and 3D flow in the hyporheic zone (Hester et al ). The modeled sequences also show features such as the “chimney effect” (Azizian et al ) where deep old upwelling hyporheic water enters the stream with little interaction with shallow flow cells (at e.g., ∼5 and 10 m).…”
Section: Resultsmentioning
confidence: 99%
“…Much of the nutrient processing carried out by streams, especially headwater streams, occurs in the hyporheic zone, defined as the region of the streambed where surface water and groundwater mix (Boano et al, ; Harvey & Gooseff, ; Hester & Gooseff, ; Krause et al, ). Static and dynamic pressure variations over the streambed surface (together with stream turbulence) drive the bidirectional exchange of water, oxygen, nutrients, and energy between the main stream channel and its surrounding sediments, a process known as hyporheic exchange (Hester et al, ). Nutrients (and other solutes) spiral downstream, alternating between relatively fast moving (often turbulent) water in the stream and relatively slow (often laminar) exchange within the hyporheic zone (Boano et al, ; Ensign & Doyle, ; Mulholland & DeAngelis, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although even for Well F4 resulting riparian travel times differ by a factor from 10 to 50 between both estimation methods, the detection of consecutive mill‐induced EC fluctuation confirmed that the positive cross‐correlation estimates are plausible for this well (Sawyer, Cardenas, Bomar, & Mackey, ). The overestimation of riparian flow times to Well F4 by the groundwater flow model may be related to the known impact of locally increased groundwater flow velocities by preferential flow paths due to high conductive layers (Beven & Germann, ; Hester, Cardenas, Haggerty, & Apte, ) or along tree roots in the riparian zone (Bargués Tobella et al, ). However, it is very unlikely that those strong discrepancies between the two methods can be explained exclusively for all wells by heterogeneity in the subsurface aquifer, particularly considering that the groundwater flow model was calibrated to the salt tracer data at the northern riparian zone.…”
Section: Discussionmentioning
confidence: 99%